Current approaches to ICT use in the preparation of future teachers of mathematics, physics and computer science (Pedagogy of Higher and Secondary Education, 2016)
The article discusses the importance of using modern computer technology and telecommunications interaction, opening new perspectives to improve the education system. In particular, the issue of analysis of modern approaches of ICT use in the preparation of future teachers of mathematics, physics and computer science has been singled out. The analysis of scientific and educational research allowed to identify the main approaches to the use of ICT in educational activities both towards the requirements of educational activities and didactic components in the educational process. The latter determines the practical value of work. The questions motivating the use of ICT in training future teachers and their future professional activities related to the lifelong learning of schooling to the profession have been discussed. In the process of education based on the ICT and related information technology not only the ICT learning, new information technology training, computer-oriented technology training, but the environment (space) as well are considered to be particularly important. The transition from a clear-cut to more flexible learning environment, in the center of which, as the subjects of the educational process, are future teachers of mathematics, physics and computer science, describes the current trend of the use of information and communication technologies, considered in the context of the creation of new educational structures, the requirements and objectives of modern education – informational and educational environment. The development of new educational system in Ukraine should lead to a new vision of the structure and content, the new results. The «new results» imply: – new opportunities for upgrading teaching methods, for restructuring the existing forms and content of education through the use of ICT; – new opportunities for getting education in higher educational institutions that use various forms of e-learning; – new opportunities for special and additional education or improving the conditions of continuous education and ICT tools used in this sphere of education.
Keywords: training future teachers; ICT; computer-oriented methodological training system; innovative ICT training fundamentalization training